Cartography and Geomedia - Medynska-Gulij, Beata; Forrest, David; Kersten, Thomas P. (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The Special Issue "Cartography and Geomedia" presents a view of cartography as a combination of technology, science, and art, with a focus on the development of geomedia in a geomatic and design-based context. Individual considerations are presented according to the following topics: efficiency of mapping techniques; historical cartographic works in a geomedial context; cartographic pragmatics for cultural heritage, teaching, and tourism; and pragmatism in gaming cartography. The main conclusion is that the two approaches to learning, revealing, and understanding geographic phenomena-starting from a specific geographical phenomenon and starting from maps and geomedia to understand geographical space-have their pragmatic strengths.